An analysis of the Excellence Initiative and its effects on the funded universities - Rainer Frietsch; Torben Schubert; Oliver Rothengatter (Expertenkommission Forschung und Innovation (EFI), 2017)
Within this study we provide descriptive as well as multivariate evidence on the effects of the German Excellence Initiative on universities. Thereby, we will focus on the question whether the Excellence Initiative has led to a sharpening of the participating universities' scientific profiles in terms of technology fields they are active in. To this end, we have created an integrated panel dataset consisting of various indicators at the level of universities. The data for the panel was collected from various sources, e.g. DESTATIS, the DFG, Web of Science by Thomson Reuters as well as PATSTAT. The results show the funding by the Excellence Initiative has been relatively concentrated with about half of the universities. In the group of universities having received funding, a few universities, often conceived as top-performers, have been successful in acquiring a substantial number of projects in all three tracks of the Excellence Initiative. A breakdown of the graduate schools and the excellence clusters by field/subject shows that the largest share of projects was awarded mathematics/natural sciences. Although we there a considerable differences between the funded and non-funded universi-ties, only few effects seem to be causally driven by the funding of the Excellence Initiative, in particular as concerns quality-related bibliometric or patent indicators. We do, however, find strong evidence that the funding of the Excellence Initiative has strongly increased the subject concentration of students and the field concentration of scientific publications. It therefore stands to reason that the Excellence Initiative has contributed to sharpening the profiles of the funded universities.
Keywords: 330